Towards adopting Zero Interest Loan (ZIL) and Profit and Loss Sharing (PLS) principle in Islamic microfinance: the case of Amanah Ikhtiar Malaysia - Md Saad, Norma; Omar Mohammad, Mustafa; S. Le, Long; Haneef, Mohamed Aslam; Abd Ghani, Mazanah (IIUM Institute of Islamic Banking and Finance, 2013)
Microfinance institutions evolved to alleviate poverty by providing micro-credit to the poor. There have been few poverty alleviation success stories from institutions such as Amanah Ikhtiar Malaysia (AIM). For the majority however, there is no solid evidence to support the positive impacts of microfinance institutions on the poor (Kono and Takahashi, 2010; as cited by Aliyu, 2012). One factor that hinders the positive impact of microfinance institutions on the poor is the inherent nature of the microcredit scheme which charges fixed and high interest rate due to high administrative cost (IRTI, 2007, as cited by Aliyu, 2012). Islamic microfinance evolved to provide alternative to the interest based conventional microfinance. However, the financing modes being used by the Islamic micro-finance institutions (IMFIs) are mostly debt based, which have resemblance to the interest based conventional modes. IMFs shun away from using the PLS scheme, which they consider risky. Theoretically, it is argued that PLS mobilizes factors of production, encourages risk sharing and ensures distributive equity in income and wealth.